Higher survival following transplantation with a mismatched unrelated donor with posttransplant cyclophosphamide-based graft-versus-host disease prophylaxis than with double unit umbilical cord blood in patients with acute myeloid leukemia in first complete remission: A study from the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation - Baron, Frédéric; Labopin, Myriam; Versluis, Jurjen; Vydra, Jan; von dem Borne, Peter A; Nicholson, Emma; Blaise, Didier; Protheroe, Rachel; Kulagin, Alexander; Bulabois, Claude Eric; Rovira, Montserrat; Chevallier, Patrice; et al. (American journal of hematology, 2024)
The best donor option for acute myeloid leukemia (AML) patients lacking an HLA-matched donor has remained intensively debated. We herein report the results of a large retrospective registry study comparing hematopoietic cell transplantation (HCT) outcomes between double-unit umbilical cord blood transplantation (dCBT, n = 209) versus 9/10 HLA-matched unrelated donor (UD) with posttransplant cyclophosphamide (PTCy)-based graft-versus-host disease (GVHD) prophylaxis (UD 9/10, n = 270) in patients with AML in first complete remission (CR1). Inclusion criteria consisted of adult patient, AML in CR1 at transplantation, either peripheral blood stem cells (PBSC) from UD 9/10 with PTCy as GVHD prophylaxis or dCBT without PTCy, transplantation between 2013 and 2021, and no in vivo T-cell depletion. The 180-day cumulative incidence of grade II-IV acute GVHD was 29% in UD 9/10 versus 44% in dCBT recipients (p = .001). After adjustment for covariates, dCBT recipients had a higher non-relapse mortality (HR = 2.35, 95% CI: 1.23-4.48; p = .01), comparable relapse incidence (HR = 1.12, 95% CI: 0.67-1.86; p = .66), lower leukemia-free survival (HR = 1.5, 95% CI: 1.01-2.23; p = .047), and lower overall survival (HR = 1.66, 95% CI: 1.08-2.55; p = .02) compared with patients receiving UD 9/10 HCT. In summary, our results suggest that transplantation outcomes are better with UD 9/10 with PTCy-based GVHD prophylaxis than with dCBT for AML patients in CR1. These data might support the use of UD 9/10 with PTCy-based GVHD prophylaxis over dCBT in AML patients lacking an HLA-matched donor.
Keywords: indukce remise; dospělí; Cyclophosphamide; cyklofosfamid; Leukemia, Myeloid, Acute; retrospektivní studie; Humans; nepříbuzný dárce; lidé středního věku; Middle Aged; akutní myeloidní leukemie; Young Adult; Hematopoietic Stem Cell Transplantation; mladý dospělý; Registries; Remission Induction; mužské pohlaví; transplantace hematopoetických kmenových buněk; Adult; Cord Blood Stem Cell Transplantation; Adolescent; nemoc štěpu proti hostiteli; Unrelated Donors; transplantace kmenových buněk z pupečníkové krve; registrace; ženské pohlaví; lidé; Graft vs Host Disease; mladiství; Aged; senioři; Male; Retrospective Studies; Female